The Relationship Between the Intensity of Social Media Use and Social Anxiety in Adolescents - Sasteri Yuliyanti; Riza Umami; Berlian Kando Sianipar (Journal of Tropical Diseases and Health Science, 2026)
The use of social media among adolescents has increased significantly. High intensity of social media use may affect adolescent mental health, one of which is social anxiety. Adolescents tend to feel afraid of negative judgments from others, which can interfere with social interactions. This study aimed to determine the relationship between the intensity of social media use and social anxiety in adolescents at SMPN 21 Bengkulu City. This study used a quantitative observational analytic design with a cross sectional approach. The population consisted of 265 students and 73 respondents were selected using proportional stratified random sampling technique. Data were collected using social media intensity and social anxiety questionnaires. Data were analyzed using univariate and bivariate (Chi-Square test) with a significance value α = 0,05. The results showed that most respondents had moderate social media use intensity, namely 63 respondents (86.3%), while most respondents experienced moderate social anxiety, namely 68 respondents (93.2%). Chi-Square analysis showed a p-value of 0.040 (p<0.05), indicating a significant relationship between the intensity of social media use and social anxiety among adolescents. There is a significant relationship between the intensity of social media use and social anxiety among adolescents. The higher the intensity of social media use, the higher the risk of social anxiety